Photobombing and Selfies: The Visibility of Atmospheric Mediation and Environing - Lila Lee-Morrison (VIEW Journal of European Television History and Culture)
Increasingly a slew of media images has highlighted the unintended capture of infrastructures of remote viewing technologies, getting in the way of seeing. These images are discussed by considering a situated view from below and on the ground, inquiring about the forms of partial and embodied visualities inscribed there. Often obscuring the visual target of scientific inquiry, these images represent both the unintentional and subjective in ways that, I argue, could be understood to communicate a visual language of photobombing and selfies, image genres that reflect an aesthetic mode of spectacle and subjectivity in the digital age. In attending to the visibility of technologies of atmospheric mediation, this article approaches the televisual infrastructures of technical objects of seeing as transforming both the field of vision and the physical environments they operate within. As these technologies become ubiquitous within the ever-congested site of the earth’s atmosphere and above, their visual capture increases an awareness of the sky as a site of distanced and unregulated perception.